PRESCHOOL ORGANIZATION AND FAMILY COOPERATION - G. H. Roziqova (Journal Park Publishing, 2023)
In this article, the love, closeness, and cooperation of family members are based on the ideology of national independence, universal values, and oriental traditions, consisting of a circle of persons bound by rights and obligations.
Keywords: parent, educator, preschool educational organization, psychologist.